Co-Gasification Characteristics of Coal and Biomass Using CO2 Reactant under Thermodynamic Equilibrium Modelling - M. Shahabuddin (MDPI AG, 2021)
This study assessed the entrained flow co-gasification characteristics of coal and biomass using thermodynamic equilibrium modelling. The model was validated against entrained flow gasifier data published in the literature. The gasification performance was evaluated under different operating conditions, such as equivalence ratio, temperature, pressure and coal to biomass ratio. It is observed that the lower heating value (LHV) and cold gas efficiency (CGE) increase with increasing temperature until the process reaches a steady state. The effect of pressure on syngas composition is dominant only at non-steady state conditions (<1100 °C). The variation in syngas composition is minor up to the blending of 50% biomass (PB50). However, the PB50 shows a higher LHV and CGE than pure coal by 12%and 18%, respectively. Overall, biomass blending of up to 50% favours gasification performance with an LHV of 12 MJ/kg and a CGE of 78%.